Reflections on the readings of Sundays and feasts: March-May 2022 - Sobb, Joseph (The Australasian Catholic record, 2022)
The annual journey through Lent to the great 'Eucharist or Thanksgiving' of the Christian 'Pasch or Passover' commences with our contemplation of Jesus in the wilderness, being tested, peirazein, by the devil, and continues next Sunday with our contemplation of Jesus on the mountain, when the disciples see him in his glory.